Multivariate analysis to simplify the differential diagnosis of broad complex tachycardia. Issue 2 (August 1991) - Griffith, M J; de Belder, M A; Linker, N J; Ward, D E; Camm, A J
Abstract : Univariate analysis has identified several criteria that aid the differential diagnosis of broad complex tachycardia. In this study of 102 consecutive patients multivariate analysis was performed to identify which of 15 clinical and 11 electrocardiographic variables were independent predictors of ventricular tachycardia. These were shown to be a history of myocardial infarction, the QRS waveforms in leads aVF and V1, and a change in axis from sinus rhythm to tachycardia of more than 40 degrees. If none of the criteria was met, the diagnosis was almost certainly supraventricular tachycardia. If one criterion was met the diagnosis was probably supraventricular tachycardia. If two criteria were met then the diagnosis was probably ventricular tachycardia. If three or four criteria were met, the diagnosis was almost certainly ventricular tachycardia. The predictive accuracy was 93%. This was increased to 95% by including two other criteria–definite independent P wave activity and ventricular extrasystoles with the same QRS configuration as that in tachycardia. These criteria were not included in the multivariate analysis because though they were 100% specific they were seldom seen. These four criteria can be used as simple rules in determining the origin of a broad complex tachycardia.